Tracheal stenosis mimicking severe acute asthma. (12th October 2010) - Zubairi, Ali Bin Sarwar; Dildar, Babar; Husain, Shahid Javed; Khan, Mohammad Faisal
Abstract : Post-intubation tracheal stenosis is a rare but serious clinical entity that rarely develops when intubation is less than a week. These patients may remain asymptomatic for a variable period and are often misdiagnosed as asthmatic. The authors report a case of a middle-aged lady who was initially misdiagnosed as having acute asthma after brief tracheal intubation.